A severe case of refractory esophageal stenosis induced by nivolumab and responding to tocilizumab therapy. Issue 1 (27th December 2018) - Horisberger, Alice; La Rosa, Stefano; Zurcher, Jean-Philippe; Zimmermann, Stefan; Spertini, Francois; Coukos, George; Obeid, Michel
Abstract : Background: The prevalence of esophageal stenosis caused by immune checkpoint inhibitors in the context of induced immune mucositis and esophagitis is extremely rare. Case presentation: We report the case of a patient with stage IV pulmonary adenocarcinoma treated for 6 months with nivolumab who developed bilateral sterile conjunctivitis followed by oropharyngeal mucositis and esophagitis complicated by a severe esophageal stenosis. The laryngeal margin and hypopharyngeal mucosa appeared highly inflammatory with fibrinous deposits. Esophagogastroduodenoscopy revealed mucositis with a scar-like structure immediately below the upper esophageal sphincter with nonulcerative mucosa and an inflammatory aspect of the entire esophagus. No involvement of the stomach was observed. Oropharynx biopsies displayed marked lymphocytic T cell-infiltration with several foci of monocellular necrosis in the squamous epithelium. No morphologic evidence of adenocarcinoma and no signs of mycotic, bacterial or viral infection were noted. A blood sample revealed a discrete increase in the erythrocyte sedimentation rate (ESR) with no eosinophilia or leukocytosis. Liver and kidney function panel tests were normal. A thoracoabdominal CT scan reported no evidence of disease recurrence. Despite multiple boluses of methylprednisolone and high doses of prednisone continued for several months, the patient experienced very rapid symptomatological reappearance during three steroid tapering attempts and aggravation of his esophageal stenosis to an aphagic stage, requiring a nasogastric tube. This long course of high-dose corticosteroid treatment was complicated with osteoporosis-induced fractures with several spontaneous compressions of thoracolumbar vertebrae requiring an enlarged T10 to L5 cementoplasty. Anti-IL-6 blockade therapy with tocilizumab resulted in excellent clinical response, allowing the total resolution of the immune-related adverse events (irAEs) and leading to successful steroid tapering. Conclusions: Herein, we describe the first case of a patient who developed autoimmune mucositis and esophagitis complicated by a severe refractory esophageal stenosis induced during treatment by nivolumab, which completely resolved after personalized treatment with tocilizumab, suggesting a role of IL-6 blockade in the management of severe steroid refractory esophageal stenosis and more broadly in refractory immune-related adverse events.